Incontinence in Intellectual Disability: An Under Recognized Cause - Nair, Lal Devayanivasudevan (J Clin Diagn Res, 2015)
Many children with Down syndrome may develop urinary incontinence during adolescence or nearing adulthood. Most often low mental ability, behavioural issues, urinary tract infection, hypothyroidism, atlanto-axial subluxation or sexual abuse may be suspected to be the reason. We report a case of Down syndrome with tethered cord syndrome (TCS) and Lipoma of Filum terminale with Cauda equina in normal position, as a cause of bowel and bladder incontinence. The need for operating with Cauda Equina in normal position is debated. But a conscious decision was taken to operate and the incontinence improved markedly which was documented by using a standardized questionnaire (King’s questionnaire) and thereby making a difference in the child’s life. A literature search did not result in any case of Down syndrome with tethered cord syndrome and secondary incontinence as presentation. Considering the possibility of TCS as a cause of incontinence, often neglected even in normal children, careful evaluation and correction of such problems will make a difference in the life of many intellectually disabled children. Incontinence should not be casually attributed to intellectual disability without ruling out other causes.